Likuiditas, Growth, dan Ukuran Perusahaan Terhadap Profitabilitas - Mas Intan Purba; Hong Neiteily Windy Milyan; Fredy Sanjaya; Teddy Tjendera (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine and analyze the effect of liquidity, growth, and company size on profitability (case studies on non-financial companies listed on the IDX for the 2018-2020 period). The research approach used is a quantitative approach. The sampling method is purposive sampling, a sample of 42 non-financial companies listed on the IDX for the 2018-2020 period multiplied by the 3 year period in the study. The results showed that the current ratio variable has a t count > t table, namely -4.062 > 1.657 and a significant value of 0.000 <0.05; b) the sales growth variable has a t count > t table, namely 3.298 > 1.657 and a significant 0.000 <0.05; c) the company size variable has a t count <t table, namely 0.932 < 1.657 and a significant 0.932 > 0.05; d) the result of F count > F table is 8.473 > 2.68 and significant 0.019 < 0.05. In conclusion, the current ratio, sales growth and firm size simultaneously have a significant effect on return on assets. The current ratio has a partially significant effect on the return on assets. Sales growth has a partially significant effect on return on assets. Company size has no significant effect partially on return on assets. Keywords: Growth, Liquidity, Profitability, Company Size